Molecular cloning and characterization of the gene encoding the DNA methyltransferase, M.CviBIII, from Chlorella virus NC-1A. - Narva, K E (1987)
The gene encoding the DNA methyltransferase, M.CviBIII, from Chlorella virus NC-1A was cloned and expressed in E. coli plasmid pUC8. Plasmid (pNC-1A.14.8) encoded M.CviBIII methylates adenine in TCGA sequences both in vivo in E. coli and in vitro. Transposon Tn5 mutagenesis localized the M.CviBIII functional domain to a 1.5 kbp region of pNC-1A.14.8 and also indicated that a virus promoter directs transcription of the gene in E. coli. The 2.1 kbp insert containing the M.CviBIII gene was sequenced and a single open reading frame of 1131 bp was identified within the domain determined by Tn5 mutagenesis. When the M.CviBIII gene was fused in-frame with the 19 amino-terminal codons of lacZ a 45 kD polypeptide was identified in maxicells as predicted by the DNA sequence. The M.CviBIII gene was not essential for virus replication since a virus M.CviBIII deletion mutant also replicated in Chlorella.